Improvement of Understanding Concept and Mathematics Problems Through Think-Pairs-Share Cooperative Learning Model on Class IX C SMP Negeri 5 Kerinci - Zahrun; Irwan; Edwin Musdi (International Conference on Education, Islamic Studies and Social Sciences Research)
Mathematics learning that occurred in SMP Negeri 5 Kerinci still centered on the teacher. Teachers tend to give concepts and formulas and how to use them, resulting in low student learning outcomes. This study aims to improve understanding of concept and problem solving ability of mathematics through cooperative type model of TPS. The research is classroom action research with 2 cycles.The subjects of this study are the students of class IX C SMP Negeri 5 Kerinci amounted to 21. This class is chosen as the subject of research because the researchers teach the class, the concept understanding and solving the mathematical problems of students are still low, the lack of attention of students in learning mathematics, and viewing the learning of mathematics is a difficult lesson and the activity of students in the classroom is limited to listening, recording and working on the problem The results showed the application of cooperative learning model type Think-Pair-Share can improve concept understanding and mathematical problem solving and based on the result of questionnaire and the interview given can improve the motivation of studying student of class IX C SMP Negeri 5 Kerinci.